A fall in isolation: reflection on a complex case. (2nd March 2023) - Chambers, Andrew
Abstract : This case review focuses on a male patient who had fallen and was found to be profoundly hypothermic, with an altered level of consciousness and evidence of seizure activity. With multiple time-critical features, this clinical presentation was made particularly challenging by the presence of several human factors. A reflective model that considered these human factors in the context of the COVID-19 pandemic, when this incident occurred, was employed. Reflecting on this incident revealed how some subconscious (intuitive) thinking led to a degree of unconscious bias compounded by availability heuristics and human factors present. This meant that the author encountered difficulty when trying to obtain peripheral vascular access and, although several alternative interventions were identified, the majority of these were unavailable at the time and some would require a change to standard clinical practice for many paramedics. The only intervention that could have been used earlier in the management of this patient was rectal diazepam, but the need for this was removed by the patient's seizure activity self-terminating. Given the increasing prevalence of falls, social isolation, mental health problems, alcohol and substance misuse, especially in the pandemic, this type of case was unlikely to be an isolated event, strengthening the argument that the range of clinical interventions available to paramedics should be increased.